Study On Time Efficiency of Tuna (thunnus sp) Catches Landing Toward Mooring Time of The Long Liner at Fishing Port of Bungus, west Sumatera Province - Zain, Jonny; ', Nardi; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A series survey activity was conducted on April-Mei 2013 at the fishing port Bungus,Padang city West Sumatera province. Purpose of this study is to know efficiency level of longliner fishing catches, which has been landed in fishing port and its factor influenced. The resultshow that the efficiency level of fishing catches landing time was 56.98-72.73%, with uploadingefficiency time was 64,65% in average. There is seven free variable influence on the timeefficiency of fishing landing, with the value r=0,836 and R2=83,6%. So the diversity ofindependent variable gives the contribution to the diversity assess of time efficiency as 83,6%.Keyword : Fishing port, long line, mooring time, time efficiency, tuna (thunnus sp)